STUDI TERHADAP PEMBELAJARAN PENDIDIKAN JASMANI OLAHRAGA DAN KESEHATAN (PJOK) SECARA DARING DI SMP NEGERI 1 RAREN BATUAH KABUPATEN BARITO TIMUR - Putra, Muhammad Diaz Arya; Ulfa, Zuly Daima; Kartiwa, Wawan (Pendidikan Jasmani, Kesehatan, dan Rekreasi, 2021)
The results of this study indicate that the implementation of PJOK learning carried out online at SMP Negeri 1 Raren Batuah is still ineffective, inadequate facilities such as networks, cellphones and lack of understanding of application problems used during learning are the main problems in this study. The impact of the online learning process is that schools must follow the curriculum and lesson plans according to the existing government circular, forcing students to have devices such as cellphones to carry out learning, but not all students have cellphones and understand online media which makes students less focused in implementing learning. So it can be concluded that the PJOK learning process conducted online at SMP Negeri 1 Raren Batuah is less effective so that it has an impact on the learning process.